Enhanced photocatalytic activity and reaction mechanism of Ag-doped α-Bi2O3 nanosheets. Issue 12 (2nd December 2017) - Shan, Lianwei; Ding, Jun; Sun, Wenli; Han, Zhidong; Jin, Liguo
ABSTRACT: The α-Bi2 O3 and Ag-doped nanosheets were successfully prepared via a citric method. Based on the sodium oxalate scavenger, it was inferred that the hole plays a key role in the photooxidation process for silver-doped Bi2 O3 . Combined further with the IR analysis, it is found that the ⋅ O 2 − has an effect on the decolorization of methylene blue (MB) under visible-light irradiation. The O2 /H2 O2 electrode could contribute to the separation of electron−hole pairs due to the electrons flowing from CB to this electrode. As a result, the doped Ag species greatly affected the photocatalytic activities of Bi2 O3 by the oxidative decolorization of MB.